Leadership Style of Trade Union Leaders and Employee Engagement: The Mediating Role of Work Motivation in Public Eye Hospital - Gautam, Niraj; Srivastava, Saurabh (NPRC Journal of Multidisciplinary Research, 2026)
Purpose: The research investigates the effects of various leadership styles- transformational, transactional, servant, and laissez-faire embraced by the trade union leaders on the engagement levels of the employees of a public eye hospital in Rupandehi district. It also discusses whether work motivation can serve as a link between these types of leadership behaviour and engagement outcomes.Methodology: The sample used was 253 unionized employees working in a hospital, and the data were collected through the help of a structured questionnaire covering a five-point Likert scale. In the analysis, descriptive statistics, structural equation modeling, and bootstrapping were used to determine both direct and mediating effects.Findings: The results suggest that the leadership styles, transactional (β = 0.361), transformational (β = 0.365), servant (β = 0.347), and laissez-faire (β = 0.207), have significant effects on the Perceived Union Leadership Support (PULS). PULS is a robust predictor of work motivation (β = 0.577) and positively and directly increases employee engagement (β = 0.470). Engagement is also positively affected by work motivation (β = 0.236), which proves the mediating role of the latter. The proposed model describes 33.3 percent of the work motivation variation and 40.4 percent of employee engagement variation. The results indicate that supportive union leadership not only enhances motivation but also fosters meaningful interaction among hospital employees.Implications: The paper highlights the revolutionary role of trade union leaders in shaping employees' experiences in public healthcare. Motivation and engagement can be reinforced through leadership development courses focused on transformational and servant leadership. The cooperation of the hospital administration with the union organisations, aimed at advancing motivation strategies and open communication, can contribute to improved morale and the quality of work.